Authority and Moral Conflicts in the Films of Adébáyọ Fálétí: Àfọ̀njá, Gáà, Ṣawo Ṣẹ̀gbẹ̀rì and the Yorùbá Cosmopolis - Olayinka Agbetuyi (Yoruba Studies Review)
In this piece, I examine the role of authority in Yorùbá society and how au[1]thority is subverted by moral conflicts generated in the political evolution of the Yorùbá state from city state to empire, leading to disastrous consequences in the society at large as presented in the films of Adébáyọ Fálétí, specifically in Àfọnjá (2002), Basọrun Gáà (2004) and Ṣawo Ṣẹgbẹ ̀ rì̀ (2005). I argue that such pains and pangs of transformation are not unique to Yorùbá society but mirror similar political evolutions in other societies such as Rome and Greece. Such political upheavals led to the celebrated assassination of Julius Caesar in Rome and Alexander the Great of Macedonia. In particular Àfọnjá ̀ and Baṣọrun ̀ Gáà dramatize evocatively the poignancy of the attendant confrontations. In addition, I evaluate Adébáyọ Fálétí as a Nigerian and African foundational practitioner in the global field of cultural studies and his use of cultural post materialism in his work. Adébáyọ Fálétí can be regarded as the father of modern Nigerian Cultural Studies and in Africa in general in line with the way that the discipline is understood the world over standing, as it were, on the cusp of traditional Nigerian and African drama and modern drama in African mother tongues. In addition, Fálétí epitomizes what modern cultural studies world-wide represent as a cross between the traditional discipline of drama and the television 172 Olayinka Agbetuyi industries as well as filmic industries, along with advertisements, which together constitute what is today known as the culture industries. As defined in the words of Chris Barker, “Culturalism focuses on meaning production by human actors in a historical context.”1 Fálétí’s historical drama and films fall within such category. Barker added that Culturalism focuses on interpretation as a way of understanding meaning.”2 These are the hallmarks of the historical drama that formed the basis of two of the films by Fálétí being examined here. In addition, he stated that cultural studies deal with subjectivity and identity or how we come to be the kinds of people we are. Fálétí’s Afọnja and Gáà’s thematic preoccupation is how the Yorùbá subjectivity has been constituted over time through its political evolution. The three films also demonstrate what Stuart Hall considers to be the connection that cultural studies seeks to make to matters of power and cultural politics.3 With regards to the role of Fálétí as pioneer in the area of radio-vision cultural industries the broadcasting mogul narrated the manner in which he pioneered the phone-in radio broadcast in Nigeria on the programme “Ѐyí Àrà” at the Broadcasting Corporation of Ọyọ̀ ́ State, Ibadan (BCOS) after pioneering Yorùbá broadcasting on Africa’s first television station Western Nigeria Television (WNTV) twenty years earlier.4 Fálétí’s career spanning close to seven decades dovetails public services with private engagement with drama production. He was one of the earliest organizers of a drama performing company in 1949 to produce his own plays. His career development can be divided into three phases: the formative traditional drama performance phase, the literary drama phase which dovetails into his career as a public servant in a symbiotic relationship and his post public service movie production phase which coincided with the efflorescence of the Nollywood. The three works examined here straddle Fálétí’s second and third phases of engagement in drama production. Both Basọrun Gáà (to be hereafter referred to as Gáà) and Ṣawo Ṣẹgbẹ ̀ rì ̀ were first staged in the second phase of Fálétí’s development as a theatre practitioner. In addition to being staged in the theater, Gáà and Ṣawo Ṣẹgbẹ ̀ rì̀ were produced for tele[1]vision audiences as dramatic thrillers and became household favourites in the ‘70s and ‘80s at the time of his career as a radio/television broadcaster. Fálétí’s retirement from public service provided the opportunity needed to build on the experience gained in the television industry to launch a full-blown film production career for which his earlier experience seems to have been a tutelage. Àfọ̀njá (2002), Gáà (2004) and Ṣawo Ṣẹgbẹ ̀ rì ̀ (2005) are part of the products of this final phase. Although Àfọ̀njá preceded the other two in movie 1 Barker, Chris. Cultural Studies: Theory and Practice. London: Sage, 2012. 2 Barker. 2012, 17 3 Barker, 5. 4 Nigerianfilms.com. February 17, 2008. Accessed Aug 10 2018. Authority and Moral Conflicts in the Films of Adébáyọ Fálétí 173 production, it was the last to be written among the three and is organically a prequel which builds on the success of Gáà and extends a thematic continuum in the Fágúnwà-esque manner of the novels Ògbójú Ọde Ninu Igbó Irunmọlẹ and Igbo Olódùmarè. While Àfọ̀njá and Gáà are historical drama based on actual events in the history of the Yorùbá Empire, Ṣawo Ṣegberi is purely fictional and is based on a postcolonial Nigerian setting. The movies therefore take a reverse order to the chronology of writing and stage performance while Ṣawo Ṣẹ̀gbẹ̀rì, which was the first to be staged among the three, was not written for stage and television performance until it was script-written for film production.5 Àfọ̀njá, Gáà and Ṣawo Ṣẹgbẹ ̀ rì ̀ are each set in a cosmopolis where the Yorùbá citizens have to deal with other nationals in the context of Yorùbá mores within a broader cosmopolitan ethos. In Àfọ̀njá and Gáà that context is provided by the empire phase of Yorùbá civilization in which Yorùbá civilization was the dominant point of reference; in Ṣawo Ṣẹgbẹ ̀ rì ̀ the drama is situated in the context of postcolonial Nigerian city, in a nation that boasts large ethnic nationalities of which the Yorùbá are only one and in which Yorùbá culture is mediated by the postcolonial state with its symbol of the English language as the means of communication and its cultural spin offs. Fálétí demonstrates the mastery of dramaturgy in Àfọ̀njá and Gáà by juxtaposing the dynamics of running a state originally built on a confederation of city state structure very much like the Greek city state structure, at the latter’s comparative stage of political evolution, with a new imperial structure and the conflicts generated by the flux of the two systems; whereas in Ṣawo Ṣẹ̀gbẹ̀rì moral conflict is generated by interpersonal amatorial clashes as well as models of expertise.